HCV Virus and Lymphoid Neoplasms. (5th July 2011) - Tsutsumi, Yutaka; Ito, Shinichi; Ogasawara, Reiki; Kudo, Kazuhiro; Tanaka, Junji; Asaka, Masahiro; Imamura, Masahiro
Abstract : Hepatitis C virus (HCV) is one of the viruses known to cause hepatic cancer. HCV is also believed to be involved in malignant lymphoma. In this paper, we investigated characteristics of malignant lymphoma cases that were anti-HCV antibody (HCV-Ab) positive. We were able to perform pathological examinations on 13 out of 14 HCV-positive cases. Of these, lymphoid tissues of 10 stained positive for HCV-Ab. There was no significant correlation between the degree of HCV staining and the rate of recurrence or resistance to treatment. However, there did appear to be a consistent decrease in the amount of HCV-RNA between pre- and posttreatment among HCV-Ab-positive cases; that is, treatment-resistant cases that exhibited resistance from the first treatment and recurrent cases more frequently had a higher HCV level at treatment termination compared to the pretreatment level. This suggests that the HCV virus either accelerates oncogenesis by direct interaction with B cells or indirectly affects lymphoma prognosis.